Reader's Digest 1,001 Computer Hints & Tips : An A-to-Z Guide to Making the Most of Your Computer and the Internet (Pleasantville, N.Y. : Reader's Digest Association, 2001)
An up-to-date collection of tips, tricks, and techniques for computer users of all levels includes step-by-step, money- and time-saving guidelines for how to get the most out of one's personal computer, covering software, hardware, the Internet, and the Windows operating system.